Displaced Communities: Can They Be Healthy? - Iris Posklinsky; Ram A. Cnaan; Hani Nouman; Limor Musayell; Odeya Shabtai Getahun (Societies, 2025)
Emergency displacement has become an increasingly salient global phenomenon, precipitated by the intensification of climate crises and persistent geopolitical conflicts. These events forcibly displace millions each year and generate complex social, political, and institutional challenges. While the literature on displacement is expanding, much of it centers on individual and household experiences, often overlooking the collective dimensions of displacement. This article addresses this gap by critically examining the concept of the displaced community, a term used to describe collectivities formed in host societies comprising individuals who have been forcibly uprooted. The article undertakes a conceptual investigation of displaced communities, seeking to define their constitutive features while accounting for their internal heterogeneity and contextual variability. To sharpen analytical clarity, the study contrasts displaced communities with healthy communities, thereby situating two polar ends of a continuum. Based on these two types of community, the question arises, “can displaced communities be healthy communities?” The article advances a conceptual model of a healthy displaced community, positing that such a construct extends conventional understandings of resilience by foregrounding the processual dynamics of recovery and adaptation. Specifically, it is argued that community health in contexts of forced displacement must be understood as the outcome of iterative processes intentionally involving community-based intervention, empowerment, and long-term sustainability. Drawing on published case studies and empirical accounts of work with displaced populations, the article demonstrates how these three pillars—community intervention, empowerment, and sustainability—are implemented in practice. It concludes with policy and practice recommendations designed to prevent further deterioration and promote the development of health and well-being within displaced communities.